CastLab: an object-oriented finite element toolbox within the Matlab environment for educational and research purposes in computational solid mechanics. (February 2019) - Richard, Benjamin; Rastiello, Giuseppe; Giry, Cédric; Riccardi, Francesco; Paredes, Romili; Zafati, Eliass; Kakarla, Santosh; Lejouad, Chaymaa
Highlights: A Matlab ® toolbox devoted to computational solid mechanics is presented An OOP architecture is adopted in order to make the toolbox flexible Case-studies illustrate the educational and user-friendly natures of the toolbox Several advanced methods to handle strain localization in solids are presented Abstract: The Matlab environment has become widely used among the computational mechanics community, not only for research purposes but also to teach either undergraduate or graduate classes. This paper aims to present a new toolbox devoted to computational mechanics and in particular to solid mechanics. Both recent and well-established numerical formulations have been implemented in it. One of its strengths resides in the fact that it was developed within an object-oriented framework. This key feature makes the CastLab toolbox easy-to-use and with extensive capabilities for customized user developments. After a brief description of the theoretical background related to the problems that can be solved by means of the toolbox, several representative case-studies are presented. These examples have been selected to illustrate not only the numerical efficiency of the toolbox, which is of primary importance for research purposes, but also its strong educational and pedagogic potential.